Proteomics of rice grain under high temperature stress - Mitsui, Toshiaki; Shiraya, Takeshi; Kaneko, Kentaro; Wada, Kaede (Frontiers in Plant Science, 2013)
Recent proteomic analyses revealed dynamic changes of metabolisms during rice grain development. Interestingly, proteins involved in glycolysis, citric acid cycle, lipid metabolism, and proteolysis were accumulated at higher levels in mature grain than those of developing stages. High temperature stress in rice ripening period causes damaged (chalky) grains which have loosely packed round shape starch granules. The high temperature stress response on protein expression is complicated, and the molecular mechanism of the chalking of grain is obscure yet. Here, the current state on the proteomics research of rice grain grown under high temperature stress is briefly overviewed.